Determination of Export Price by Incoterms 2010 (Study in PT X Karawang) - Rima Sundari; Edi Supardi (TRIKONOMIKA, 2015)
Determination of export price will give influences to company’s profit, image, and the competitiveness in the customers perspectives. Determination of export price must be based on the applied international standards which refer to the International Commercial Terms or Incoterms. Incoterms always updated to follow developments of international trading therefore any Incoterms changes that occur will affect the determination. The calculation of export price based on Incoterms is calculated based on cost of goods production, benefits, cost of packaging, loading costs, transportation, taxes and fees and the cost of transportation insurance. The results showed that most often-used Incoterms by company in gradation are FOB, CFR and CIF. Lastly, the higher use of Incoterms class by company has positive influence to increase corporate profit.